Development and shielding effectiveness characterization of a three-layer polycarbonate-nickel-aluminum electromagnetic shield - De Guzman, Eric M. (Animo Repository, 2004)
This research aims to develop and characterize the shielding effectiveness (SE) of a three-layer electromagnetic shield composed of polycarbonate, nickel and aluminum. The developed shield uses polycarbonate film as a substrate coated with varying thickness of aluminum and fixed nickel. Polycarbonate film was chosen over the other non-conductive materials because of its physical and thermal properties such as flexibility and thermoformability. Nickel has a high adherence to non-conductive surface while aluminum has a high shielding effectiveness and low melting point. This study used the experimental approach in gathering data for evaluation and analysis. The high vacuum coating machine was used to evaporate nickel and aluminum on polycarbonate film in order to fully realize the development of the shield. The spectrum analyzer and RF Generator were used to characterize their shielding performance. Adhesion tests were also conducted to justify the existence of nickel as the primary coating. The shielding effectiveness of nickel and aluminum were measured and compared. A two-layer and three-layer electromagnetic shield was also characterized and the results were compared. Grounded and ungrounded modes of testing and shielding performance were included for nickel, aluminum, and their combination. Aside from the measured shielding effectiveness, a mathematical computation of SE was included to compare the predicted and measured values. Results indicated that with 75 nanometer thickness, the SE of aluminum is 16.2% higher than nickel. Nickels adherence strength is 55.4% higher than aluinum. The three-layer shield SE is 20% higher than the two-layer shield if the coating is aluminum and 41% higher if the coating of the two-layer shield is nickel. Reflection, absorption and multiple reflection coefficient all contribute to the total shielding effectiveness. In a three-layer shield, ungrounded SE is 29.7% lower than the grounded shield. For a two-layer shield, the SE of the ungrounded nickel coated shield is 32% lower than the grounded shield. The SE of the ungrounded aluminum shield is 22.5% lower than when the shield is grounded.